Diabetic retinopathy as the leading cause of blindness and early predictor of cascading complications-risks and mitigation - Kropp, Martina; Golubnitschaja, Olga; Mazurakova, Alena; Koklesova, Lenka; Sargheini, Nafiseh; Vo, Trong-Tin Kevin Steve; de Clerck, Eline; Polivka, Jiri; Potuznik, Pavel; Polivka, Jiri; Stetkarova, Ivana; Kubatka, Peter; et al. (The EPMA journal, 2023)
Proliferative diabetic retinopathy (PDR) the sequel of diabetic retinopathy (DR), a frequent complication of diabetes mellitus (DM), is the leading cause of blindness in the working-age population. The current screening process for the DR risk is not sufficiently effective such that often the disease is undetected until irreversible damage occurs. Diabetes-associated small vessel disease and neuroretinal changes create a vicious cycle resulting in the conversion of DR into PDR with characteristic ocular attributes including excessive mitochondrial and retinal cell damage, chronic inflammation, neovascularisation, and reduced visual field. PDR is considered an independent predictor of other severe diabetic complications such as ischemic stroke. A "domino effect" is highly characteristic for the cascading DM complications in which DR is an early indicator of impaired molecular and visual signaling. Mitochondrial health control is clinically relevant in DR management, and multi-omic tear fluid analysis can be instrumental for DR prognosis and PDR prediction. Altered metabolic pathways and bioenergetics, microvascular deficits and small vessel disease, chronic inflammation, and excessive tissue remodelling are in focus of this article as evidence-based targets for a predictive approach to develop diagnosis and treatment algorithms tailored to the individual for a cost-effective early prevention by implementing the paradigm shift from reactive medicine to predictive, preventive, and personalized medicine (PPPM) in primary and secondary DR care management.
Keywords: ROS; Stress; Proliferative diabetic retinopathy; Biomarkers; Cerebral small vessel disease; Retinopathy; Diabetic complications; Mitochondrial injury; Diabetes mellitus; Cell death; Comorbidities; Metabolic and signalling shifts; Tear fluid; Blindness; Inflammation; Domino effect; Primary and secondary prevention; Global burden; Neovascularisation; Ischemic stroke; Predictive, preventive, and personalised medicine (3P/PPPM); Health policy; Health-to-disease transition; Analytical tools; Molecular patterns